Altered neurochemical ingredient of hippocampus in patients with bipolar depression - Atmaca, Murad; Yildirim, Hanefi (My University, 2012)
Background. In a number of investigations, hippocampal neurochemicals were evaluated in the patients with bipolar disorder who were on their first episode or euthymic periods. However, we did not meet any investigation in which only patients with bipolar depression were examined. As a consequence, the objective of the present study was to examine both sides of hippocampus of patients with bipolar disorder in depressive episode and healthy controls using 1H-MRS. Methods. Thirteen patients with DSM-IV bipolar I disorder, most recent episode depressed, were recruited from the Department of Psychiatry at Firat University School of Medicine. We also studied 13 healthy comparison subjects who were without any DSM-IV Axis I disorders recruited from the hospital staff. The patients and controls underwent proton magnetic resonance spectroscopy (1H-MRS) of their hippocampus. NAA, CHO, and CRE values were measured. Results. No significant effect of diagnosis was observed for NAA/CRE ratio. For the NAA/CHO ratio, the ANCOVA with age, gender, and whole brain volume as covariates revealed that the patients with bipolar depression had significantly lower ratio compared to healthy control subjects for right and for left side. As for the CHO/CRE ratio, the difference was statistically significant for right side, with an effect diagnosis of F = 4.763, P = 0.038, and was very nearly significant for left side, with an effect diagnosis of F = 3.732, P = 0.064. Conclusions. We found that the patients with bipolar depression had lower NAA/CHO and higher CHO/CRE ratios compared to those of healthy control subjects. The findings of the present study also suggest that there may be a degenerative process concerning the hippocampus morphology in the patients with bipolar depression. © 2012 Murad Atmaca and Hanefi Yildirim.